Antikeloid Activity and Irritation Test of Combination Extract of Tithonia diversifolia A. Gray and Nerium indicum Mill in vivo - Yuliani, Fara Silvia; Wahyuningsih , Mae Sri Hartati (Universitas Tidar, 2024)
Keloids, marked by overgrowth of fibrous tissue beyond wound boundaries, present therapeutic challenges due to recurrence and the side effects of current treatments. Conventional methods, including surgery and radiotherapy are often costly and carry risks such as recurrence, pain, and infection. This has led to increasing interest in natural alternatives. This study investigates the antikeloid potential of a combination extract from Nerium indicum Mill (N. indicum) and Tithonia diversifolia A. Gray (T. diversifolia) in an in vivo rabbit ear hypertrophic scar model. The efficacy of the extract was evaluated using the Scar Elevation Index (SEI), while irritation tests assessed its potential for localized skin reactions. Five groups were tested: three groups receiving different doses of the combination extract, a negative control (aquadest), and a positive control (triamcinolone acetonide). The results showed that SEI values in all treatment groups were significantly reduced compared to the negative control (p<0.05), indicating reduced scar prominence. The Draize test further classified the extract as a minimal irritant, supporting its safety for topical application. These findings suggest that the combination extract of N. indicum and T. diversifolia is a promising, safer, and natural alternative for keloid treatment, particularly in managing hypertrophic scars.